Morning hours lectures on God's existence - Mendelssohn, Moses 1729-1786 (Studies in German idealism, 2011)
Morning Hours is the only available English translation of Morgenstunden by Moses Mendelssohn, the foremost Jewish thinker of the German Enlightenment. Published six months before Mendelssohn's death on January 4, 1786, Morning Hours is the most sustained presentation of his mature epistemological and metaphysical views, all elaborated in the service of presenting his son with proofs for the existence of God. But Morning Hours is much more than a theoretical treatise. It also plays a central role in the drama of the Pantheismusstreit, Mendelssohn's "dispute" with F. H. Jacobi over the nature and scope of Lessing's attitude toward Spinoza and "pantheism". In Morning Hours Mendelssohn attempts to set the record straight regarding his beloved Lessing in this connection, not least by demonstrating the absence of any practical difference between theism and a "purified pantheism". - Publisher's description.